CONSUMPTION ETHICS IN ISLAMIC MICROECONOMICS AND ITS IMPACT ON FAMILY WELFARE - Tulus Budi Santoso; Muhammad Hamdan Ali Masduqie (Jurnal Dinamika Ekonomi Syariah, 2026)
This study investigates the impact of Islamic microeconomic consumption ethics on Muslim family welfare by emphasizing empirical outcomes and their practical implications. Using survey data from 120 Muslim households collected through random sampling and analyzed with simple linear regression, the findings demonstrate a strong and statistically significant relationship between Islamic consumption behavior and family welfare (p < 0.05). The coefficient of determination (R² = 0.74) indicates that the implementation of Islamic consumption principles explains a substantial proportion of welfare variation. Empirical results reveal that adherence to halal and thayyib consumption, the avoidance of israf (excessive spending), and the prioritization of needs based on the hierarchy of dharuriyat, hajiyat, and tahsiniyat significantly enhance financial stability, psychological well-being, and social harmony. Moreover, the integration of zakat and charitable practices strengthens household resilience and reinforces social solidarity. These findings confirm that Islamic consumption ethics function not merely as normative religious guidelines but as an effective microeconomic mechanism for promoting sustainable family welfare and achieving falah through the integration of material and spiritual dimensions.